WCSim: A Cloud Computing Simulator with Support for Bag of Tasks Workflows - Santos, Maicon Ança dos; Grabher, Gabriel J. A.; Kovaleski, Matheus F.; Geyer, Cláudio F. R.; Cavalheiro, Gerson Geraldo H. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2023)
In this paper, we present WCSim, Workflow Cloud Simulator. Firstly, we argue that this cloud simulation tool offers a high level of accessibility by allowing the description of various components, such as users, infrastructures, and workload, of a given scenario simply by providing parameters at launch time, without requiring the extension of the simulator code. Then, we explain how we conceived the components for the simulation models and provide a detailed description of the implemented software. Additionally, we compare the results of a small scenario obtained from two other simulation tools with those provided by WCSim. Finally, we present a case study that illustrates the usage of WCSim. The paper also introduces the a abstraction to model workflows as a Direct Acyclic Graph of Bag of Tasks.